1992
DOI: 10.1016/0014-5793(92)80250-k
|View full text |Cite
|
Sign up to set email alerts
|

Two sites of primary degradation of the D1‐protein induced by acceptor or donor side photo‐inhibition in photosystem II core complexes

Abstract: Depending on experimental conditions wc have found that photo-inhibitory treatment of photosystem II (PSIl)core complexes, isolated from wheat, can generate Iwo fragmenls of about 23-24 kDa that contain either the C-terminal or N-terminal regions of the Dl-prouin. A 24 kDa Gterminal fragment appears when the water splitting reaction is not functional and an electron acceptor is present. This'donor'.side inhibition also generates an N-terminal fragment of about IO kDa and is suggested to be due to the cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 29 publications
6
78
0
Order By: Relevance
“…Our data demonstrate that, under our experimental conditions, the 18-kDa peptide arises from the C terminus of the D1 protein and includes the portions of the D-de loop bearing the antigenic determinants for the D-de loop antibody. A number of other laboratories, using a variety of experimental protocols, have observed a D1 fragment of similar apparent molecular mass (27)(28)(29). The higher molecular mass bands at 52 and 68 kDa are aggregates containing D1 and possibly other protein components.…”
Section: Resultsmentioning
confidence: 93%
“…Our data demonstrate that, under our experimental conditions, the 18-kDa peptide arises from the C terminus of the D1 protein and includes the portions of the D-de loop bearing the antigenic determinants for the D-de loop antibody. A number of other laboratories, using a variety of experimental protocols, have observed a D1 fragment of similar apparent molecular mass (27)(28)(29). The higher molecular mass bands at 52 and 68 kDa are aggregates containing D1 and possibly other protein components.…”
Section: Resultsmentioning
confidence: 93%
“…Its breakdown products have been identified both in rive [27] and in vitro [10,11], and the existence of specific pathways for D1 degradation depending on whether donor or accepter side photoinhibition is involved, has been proven [17][18][19]. Accepter side photoinhibition is thought to produce cleavage in the hydrophobie loop connecting the 3rd and 4th transmembrane segments [27], whilst donor side photoinhihition probably leads to a cleavage in the loop connecting the 1st and 2nd and the 3rd and 4th transmembrane segments [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some light-induced fragments have been isolated and characterized [15] and there is now agreement that degradation of the protein may proceed Abbreviat&ns: cyt, cytochrome; DBMIB, 5-dibromo-3-methyi-6-isopropyl-p-b~nzoquinone; PMSF, phenyl-methane-sulphonyl fluoride; PSII, photosystem 11; PVDF, polyvinylidene difiuoride; RCII, reaction center complex of photosystem It. along different pathways, depending on whether its degradation is triggered by damage at the donor or aeceptor sides [17][18][19]. Some photodegradation products of the D2 protein have also been detected [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although light energy is a specific requirement for the production of stored chemical energy, too much light is known to inhibit photosynthesis and damage the photosynthetic apparatus (Kok, 1956;Kyle et al, 1984;Ohad et al, 1984). The main site of this inhibitory effect has been located in photosystem I1 (PSII; Powles, 1984), and has been linked to the turnover of one of the central reaction centre components, the D1 protein, which is the product of the psbA gene (Prasil et al, 1992;Barber and Andersson, 1992). It has also been shown that another reaction centre protein, which is encoded by the psbD gene, is degraded as a consequence of illumination with high light intensities (Schuster et al, 1988), although D2 is found to be relatively stable at low light levels (Gounaris et al, 1987).…”
mentioning
confidence: 99%